Floral Developmental Morphology and Biochemical Characteristics of Male Sterile Mutants of Lagerstroemia indica - Fuyuan Deng; Liushu Lu; Lu Li; Jing Yang; Yi Chen; Huijie Zeng; Yongxin Li; Zhongquan Qiao (Plants)
Male sterility is a common phenomenon in higher plants and often plays an important role in the selection of superior offspring. ‘Xiang Yun’ is a mutant of Lagerstroemia indica that does not bear fruit after flowering, and its flowering period is significantly longer than that of normal L. indica. To explore the timing and molecular mechanisms of sterility in ‘Xiang Yun’, this study determined the period of sterility through anatomical observation and compared the content of nutrients and the activity of antioxidative enzymes at different stages of flower development. Finally, sequence alignment and qPCR were used to analyze the differences in pollen development genes between ‘Xiang Yun’ and ‘Hong Ye’. The results showed that the anthers of ‘Xiang Yun’ dispersed pollen normally, but the pollen grains could not germinate normally. Observations with scanning electron microscopy revealed that the pollen grains were uneven in size and shriveled in shape. Further observation of anther sections found that abnormal development of the microspores began at the S2 stage, with the callose wall between microspores of ‘Xiang Yun’ being thicker than that of ‘Hong Ye’. In addition, during the flower development of ‘Xiang Yun’, the contents of soluble sugar, soluble protein, free proline, and triglycerides were deficient to varying degrees, and the activities of POD, SOD, and MDA were lower. Sequence alignment and qPCR showed that there were several mutations in EFD1, TPD1, and DEX1 of ‘Xiang Yun’ compared with ‘Hong Ye’, and the expression levels of these genes were abnormally elevated in the later stages of development. Our results clarified the timing and phenotype of male sterility in ‘Xiang Yun’. This provides solid and valuable information for further research on the molecular mechanism of sterility in ‘Xiang Yun’ and the genetic breeding of crape myrtle.